Periostin-expressing Schwann cells and endoneurial cardiac fibroblasts contribute to sympathetic nerve fasciculation after birth - Hortells, Luis (J Mol Cell Cardiol, 2021)
BACKGROUND: The intracardiac nervous system (ICNS) is composed of neurons, in association with Schwann cells (SC) and endoneurial cardiac fibroblasts (ECF). Besides heart rhythm control, recent studies have implicated cardiac nerves in postnatal cardiac regeneration and cardiomyocyte size regulation, but cardiac SC and ECF remain understudied. During the postnatal period, the ICNS undergoes intense remodeling with nerve fasciculation and elongation throughout the myocardium, partially guided by the extracellular matrix (ECM). Here we report the origins, heterogeneity, and functions of SC and ECF that develop in proximity to neurons during postnatal ICNS maturation. METHODS AND RESULTS: Periostin lineage (Postn+) cells include cardiac Remak SC and ECF during the postnatal period in mice. The developmental origins of cardiac SC and ECF were examined using Rosa26(eGFP) reporter mice bred with Wnt1Cre, expressed in Neural crest (NC)-derived lineages, or tamoxifen-inducible Tcf21MerCreMer, expressed predominantly in epicardial-derived fibroblast lineages. ICNS components are NC-derived with the exceptions of the myelinating Plp1+ SC and the Tcf21+ lineage-derived intramural ventricular ECF. In addition, Postn+ lineage GFAP- Remak SC and ECF are present around the fasciculating cardiac nerves. Whole mount studies of the NC-derived cells confirmed postnatal maturation of the complex ICNS network from P0 to P30. Sympathetic, parasympathetic, and sensory neurons fasciculate from P0 to P7 indicated by co-staining with PSA-NCAM. Ablation of Postn+ cells from P0 to P6 or loss of Periostin leads to reduced fasciculation of cardiac sympathetic nerves. In addition, collagen remodeling surrounding maturing nerves of the postnatal heart is reduced in Postn-null mice. CONCLUSIONS: Postn+ cells include cardiac SC and ECF during postnatal nerve maturation, and these cells have different embryonic origins. At P7, the Postn+ cells associated with cardiac nerves are mainly Remak SC and ECF. Ablation of the Postn+ cells from P0 to P6 and also loss of Postn in Postn-null mice leads to reduced fasciculation of cardiac nerves at P7.